Ṭamil Nāḍū meṉ naʻt goʼī / ʻAlīm Ṣabā Navīdī ; murattabah, Jāvīdah Ḥabīb. - Ṣabā Navīdī, ʻAlīm. (Ṭamil Nāḍū Urdū Pablīkeshanz ; Kitāb milne [kā patā], Maktabah Jāmiʻah, 2004)
On the history and development of naʻt (poems in praise of Prophet Muḥammad, d. 632) in Tamil Nadu; includes poetry (naʻt) of some selected poets.